Are Large Firms Born or Made? : Evidence from Developing Countries - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2015)
This paper uses survey data from 120 developing countries to compare the role of institutions with firm characteristics at the time of creation of the firm in explaining the size, growth, and productivity of firms over their lifecycle. The study finds that firm-level characteristics have comparable, and sometimes even larger, power than institutional factors in predicting size and growth, but not productivity. In particular, size at birth plays a key role in predicting variation in firm size and growth since birth over the firm lifecycle, whereas country factors dominate in predicting variation in labor productivity over the firm lifecycle. The study also finds that older firms are larger, partly because of the selection of more efficient firms. The findings point to the importance of initial founding conditions in explaining variations in size and growth over the firm lifecycle across countries.